KOMPOSISI JENIS KAYU YANG DIGUNAKAN DALAM KONSTRUKSI JALAN REL DI HUTAN RAWA SUMATERA DAN KALIMANTAN - Dulsalam Dulsalam; Apul Sianturi (Jurnal Penelitian Hasil Hutan, 1985)
Data collected consist of the diameters and lengths of wood used in railroad construction in swamp forests of ten forest companies in Sumatera, and six in Kalimantan. Railroads in the swamp forests are different in construction compared to those in the teak forests, generally requiring four layers of sleepers.  This, of course, is due to the extremely low bearing capacity of the soil little is known about the problems of this type of railroad construction, primarily with regard to the quantity of wood required.The steps of collecting data were as follow:Selecting suitable forest companies in Sumatera and in Kalimantan to be surveyed.In each forest area 20 samples of 50 m rail track sections were drawn systematically.Diameters and lengths of logs within the sections were measured according to layers.The average amount of wood used in swamp forests railroad in Sumatera and Kalimantan are respectively 142 m3/km and 188 m3/km. The volume of wood used in every km of railroad between regions are significantly different, and those among forest companies very significantly.Wood used in every km of railroad construction and for layer of sleepers vary. The average of wood used for railroad construction of the 1st and 2nd layer in Sumatera are respectively 55 m3  /km and 87 m3/km.  Those in Kalimantan consist of four layers of sleepers, i.e.:   Ist, 2nd,  3rd and 4th layer from the  top-down,  averaging 32 m3lkm, 64 m3/km, 74 m3/km and 18 m3/km of wood used per layer respectively.